Cathodes for Electrochemical Carbon Dioxide Reduction to Multi-Carbon Products: Part II : Rapid improvement in cathode performance. Issue 1 (31st January 2023) - Macpherson, Harry; Hodges, Toby; Chuma, Moyahabo Hellen; Sherwin, Connor; Podbevšek, Urša; Rigg, Katie; Celorrio, Veronica; Russell, Andrea; Corbos, Elena C.
This is Part II of a focused review of recent highlights in the literature in cathode development for low temperature electrochemical carbon dioxide and carbon monoxide reduction to multi-carbon (C2+) products. Part I (1) introduced the role of CO2 reduction in decarbonising the chemical industry and described the catalysts and modelling approaches. Part II describes in situ characterisation to improve the understanding and development of catalysts, the catalyst layer and the gas diffusion layer.